Postdiagnosis Physical Activity and Dietary Inflammatory and Insulinemic Potential with Overall Survival in Men with Nonmetastatic Prostate Cancer - De Moraes-Ferrari, G (Springer Science and Business Media B.V., 2025)
Inflammation and insulin resistance are associated with increased mortality in the general population. However, it remains unclear how physical activity and proinflammatory/hyperinsulinemic diets influence overall survival in prostate cancer patients. We analyzed 4779 men with nonmetastatic prostate cancer from the Health Professionals Follow-up Study. Postdiagnosis physical activity and diet were assessed using validated self-reported questionnaires. We used the validated dietary scores to empirically assess the anti-inflammatory (rEDIP) and anti-insulinemic (rEDIH) potential of dietary patterns based upon specific combinations of food groups. Cox regression model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). During a median of 15 years of follow-up, we identified 2282 deaths. Compared to men with < 3 MET-h/week of postdiagnosis physical activity, multivariable-adjusted HRs (95% CI) were 0.80 (0.68–0.95) for 9-< 24 MET-h/week, 0.63 (0.53–0.75) for 24-< 48 MET-hours/week and 0.61 (0.51–0.73) for ≥ 48 MET-hours/week in relation to all-cause mortality (P-trend < 0.001). Both vigorous and non-vigorous activities after diagnosis were associated with lower all-cause mortality (P-trend < 0.001). Moreover, post-diagnosis rEDIP and rEDIH scores were inversely associated with all-cause mortality (HR per 1-SD increase: 0.93 (0.89–0.99) for rEDIP; 0.91 (0.86–0.96) for rEDIH). In joint analyses, men with high physical activity and high rEDIP (or rEDIH) score showed approximately 30–36% lower risks of all-cause mortality, compared to those with low physical activity and low diet scores. In conclusion, high physical activity and low proinflammatory and hyperinsulinemic diets were independently associated with decreased risk of all-cause mortality in men with prostate cancer. Men with both high physical activity and low proinflammatory and hyperinsulinemic diets after diagnosis have the lowest mortality rate. © Springer Nature B.V. 2025.